Speech and Voice in the Comic Performances of the Traditional Greek Shadow Theatre of Karaghiozis (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
The article presents the aesthetics and the main features of speech and voice of the Modern Greek shadow theatre of Karaghiozis, concentrating mainly on the comic repertoire. The period of reference is the years of its peak from the 1890s to the 1960s. The article argues that speech and voice were the primary mediums of expression. The shadow-theatre player, hidden behind the screen, used mostly linguistic signs to animate the two-dimensional flat puppets and narrate the story.Keywords: Modern Greek Shadow Theatre, Oral Culture, Urban Culture.